1979
DOI: 10.1113/jphysiol.1979.sp012603
|View full text |Cite
|
Sign up to set email alerts
|

Changes in total and quantal release of acetylcholine in the mouse diaphragm during activation and inhibition of membrane ATPase.

Abstract: SUMMARY1. Acetylcholine (ACh) released from mouse diaphragm was gel filtrated and estimated by bio-assay and compared with electrophysiologically measured quantal release, expressed either as frequency of miniature end-plate potentials or quantum content of end-plate potentials.2. Activation of Na+-K+-dependent membrane ATPase (membrane ATPase) in Na+-loaded muscles lowered the total amount of ACh released at rest to one tenth of the control value, but quantal release remained unchanged.3. Inhibition of membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
2

Year Published

1981
1981
1993
1993

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(57 citation statements)
references
References 22 publications
4
51
2
Order By: Relevance
“…3) were greater than in nor mal mice. An electrophysiological study has shown that ACh is released mainly in a nonquantal manner at rest, whereas quantal release also occurred spontaneously, generating miniature end-plate potential (17). The non quantal ACh leakage from the motor nerve terminal is in creased by ouabain, a Na+,K+-ATPase inhibitor (18).…”
Section: Discussionmentioning
confidence: 99%
“…3) were greater than in nor mal mice. An electrophysiological study has shown that ACh is released mainly in a nonquantal manner at rest, whereas quantal release also occurred spontaneously, generating miniature end-plate potential (17). The non quantal ACh leakage from the motor nerve terminal is in creased by ouabain, a Na+,K+-ATPase inhibitor (18).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitters are released from nerve terminals in two ways: by the continuous leakage of individual molecules across the nerve terminal membrane (23,33,41,50) and by synchronous secretion of few thousands molecules in packages, or quanta (14,15,20). Quantal secretion causes the changes in membrane potential that excite the postsynaptic cell, and transmission at a synapse is critically dependent upon this mechanism of release.…”
mentioning
confidence: 99%
“…The spontaneous release of ACh includes that released quantally which causes m.e.p.ps and that released non-quantally to cause a small depolarization of the endplate region equivalent to that produced by about 10-8M ACh in the frog (Katz & Miledi, 1977), 10-7M in mice (Vyskocil et al, 1983) and 6 x 10-9M in rats (Smith, 1984). In unstimulated tissues, the amount released non-quantally from the nerve is about ten times greater than that released quantally (Miledi et al, 1983 & Vyskocil, 1979;Dolezal & Tucek, 1983;Stanley & Drachman, 1983) and is from the cytoplasm of the nerve (Molenaar et al, 1987 (Adams et al, 1986). In this regard, Jenkinson & Nicholls (1961) and Takeuchi (1963) reported abolition by Mg2+ of the local contracture normally found after ACh.…”
Section: Methodsmentioning
confidence: 99%